2022
DOI: 10.3389/fbioe.2021.820434
|View full text |Cite
|
Sign up to set email alerts
|

Light-Triggered Adhesive Silk-Based Film for Effective Photodynamic Antibacterial Therapy and Rapid Hemostasis

Abstract: Successful control of massive hemorrhage in deep wounds with irregular shape and low elasticity still remains great challenges in the clinic. As the wound sites are usually at risk of bacterial infection, it is necessary to design an ideal hemostatic agent with rapid hemostasis and excellent antibacterial activity. In this study, we developed a light responsive hemostatic film for effective handling of liver bleeding with promising photodynamic therapy against S. aureus onnear infrared (NIR) irradiation. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…SF films have been vastly applied for wound dressing materials in numerous studies. Recently, Huang et al reported a light-triggered SF-based film with effective antibacterial activity for hemostatic applications [74]. In this study, they developed a light-responsive SF film to effectively manage liver hemorrhage with effective treatment against S. aureus SF films are a candid biomaterial of choice for biomedical applications owing to their intrinsically less complex character regarding scaffold development.…”
Section: Sf Sponge/filmmentioning
confidence: 98%
See 1 more Smart Citation
“…SF films have been vastly applied for wound dressing materials in numerous studies. Recently, Huang et al reported a light-triggered SF-based film with effective antibacterial activity for hemostatic applications [74]. In this study, they developed a light-responsive SF film to effectively manage liver hemorrhage with effective treatment against S. aureus SF films are a candid biomaterial of choice for biomedical applications owing to their intrinsically less complex character regarding scaffold development.…”
Section: Sf Sponge/filmmentioning
confidence: 98%
“…Recently, Huang et al reported a light-triggered SF-based film with effective antibacterial activity for hemostatic applications [74]. In this study, they developed a light-responsive SF film to effectively manage liver hemorrhage with effective treatment against S. aureus on near-infrared (NIR) irradiation.…”
Section: Sf Sponge/filmmentioning
confidence: 99%
“…The wound-healing process proceeds in four phases: hemostasis, inflammation, proliferation, and remodeling . Among these, uncontrollable bleeding and bacterial infection are the main challenges in the early stages of wound healing. , To stop bleeding quickly and prevent infection, wounds are often treated clinically with hemostatic materials and antibiotic drugs. , Currently, there are many clinically available hemostatic materials, such as conventional wound dressing, , microporous aluminosilicates (zeolites and clays), , or various polymer-based materials (e.g., hydrogels, sponges, and films). Although all of them have hemostatic functions, they still have some disadvantages. For example, conventional wound dressings are usually less effective and need long-term treatment .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanomaterials have gradually attracted great interest due to their unique characteristics, including small size, easy modification, and high reactivity (Biju, 2014;Zhou et al, 2018b;Wu et al, 2020;Tang et al, 2021;Zheng et al, 2021). Particularly, they have been widely applied in biomedical fields, such as tissue engineering, bioimaging, cancer therapy, and antibacterial applications (Ku et al, 2013;Zhou et al, 2016;Liguori et al, 2019;Tang X. et al, 2020;Makabenta et al, 2021;Wang et al, 2021;Huang et al, 2022;Song et al, 2022). Among various nanomaterials, magnetic nanoparticles (MNPs), which have been approved by the U.S. Food and Drug Administration (FDA), received considerable attention for their broad biomedical applications (e.g., magnetic resonance imagining, diagnostics, drug delivery, hyperthermia, etc.)…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%